Perspectives on security and strategic stability: a track 2 dialogue with the Baltic states and Poland - Sawyer Samp, Lisa; Rathke, Jeffrey; Bell, Anthony (CSIS Reports, 2016)
This study presents the outcome of a Track II dialogue among civil society leaders, security experts, academics, and government representatives from across the Baltic States, Poland, and the United States who came together to discuss the shared threats and challenges facing NATO's eastern flank in light of Russia's aggressive behavior toward its neighbors. The objective of the study was to enhance scholarship on the challenges stemming from the Ukraine crisis and to inform public discussions on the evolving nature and future of security and defense relations among the United States, the Baltic States, and Poland.